Complete compression ultrasonography of the leg veins as a single test for the diagnosis of deep vein thrombosis - Schellong, Sebastian M.; Schwarz, Thomas; Halbritter, Kai; Beyer, Jan; Siegert, Gabriele; Oettler, Wolfram; Schmidt, Benjamin; Schroeder, Hans E. (Thrombosis and Haemostasis, 2003)
Noninvasive diagnosis of deep vein thrombosis (DVT) is based on ultrasound examination of the leg veins, usually restricted to only compression of the proximal veins (CUS). Patients with negative CUS findings require a second examination or a combination with other tests, which impairs clinical efficiency. In this prospective outcome study, 1646 consecutive patients with clinically suspected DVT were examined once by a standardized protocol of complete compression ultrasound comprising all proximal and distal veins (CCUS) as the only diagnostic test. The examination was equivocal in 15 patients (1% technical failure rate). Another 366 patients (22%) were tested positive for proximal DVT, distal DVT, muscle vein thrombosis, or phlebitis. Of 1265 patients in whom CCUS findings were negative, 242 met exclusion criteria for follow-up (age <18, life expectancy <3 months, other reasons for anticoagulation, postthrombotic lesions of the leg veins, or lack of informed consent). During the 3 months of follow-up, three of 1023 patients with negative CCUS findings experienced a symptomatic venous thromboembolic event (0.3% [95% CI 0.1%-0.8%]). We conclude that the CCUS protocol has a low technical failure rate and is safe with respect to excluding DVT, thereby reducing the diagnostic workup of patients with suspected DVT to a single ultrasound examination.
Keywords: Deep vein thrombosis; diagnosis; ultrasound